Polydimethyl siloxane nanocomposites: Their antifouling efficacy in vitro and in marine conditions. (October 2015) - Gomathi Sankar, G.; Sathya, S.; Sriyutha Murthy, P.; Das, Arindam; Pandiyan, R.; Venugopalan, V.P.; Doble, Mukesh
Abstract: Polydimethyl siloxane (PDMS), in spite of possessing excellent foul-release properties, is prone to microbial fouling caused by organisms such as bacteria and diatoms. In the present study, we incorporated metal oxide nanoparticles in PDMS matrix to create composites with enhanced antifouling properties. The nanocomposites were prepared by incorporating small amounts (0.1 wt per cent) of CuO, CTAB-capped CuO and ZnO nanoparticles in PDMS. Their antibiofilm properties were tested in vitro against a marine bacterium and a diatom and also in the field. ZnO nanocomposite, exhibiting highest hydrophobicity, surface roughness and good antimicrobial activity, prevented biofouling in the sea for 45 days. PDMS with CTAB-capped CuO showed minimum roughness and hydrophobicity and performed well against the bacterium Bacillus flexus and the diatom Navicula sp. Metal leaching rates from the nanocomposites were quite low when compared to reported data, indicating that environmental effects of the nanocomposites would be minimal. The study indicates that the antifouling property of a foul-release polymer such as PDMS can be further increased by incorporation of nanoparticles, so that the formulation remains fouling-free even without extra shear forces. Highlights: 80% reduction in fouling is noticed with ZnO nanocomposite after 45 days in the field. Hydrophobicity of PDMS is increased significantly after adding ZnO nanoparticles. Low metal leaching of nanocomposites, indicating minimal environmental effects.